P28 Which factors influence end of life care provision in patients with advanced chronic liver disease: Lessons from the South West. (20th September 2022) - Maggs, Daniel; Saunsbury, Emma; Masterman, Benjamin; Belfield, Katherine; Bendall, Oliver; Betteridge, Frederica; Emms, Holly; Godlee, Sarah; Gormley, Sarah; Gurung, Dilip; Katwal, Prakash; Knowles, Laurence; et al.
Abstract : Introduction: End of life care (EOLC) refers to care given to patients who are likely to be within their last year of life. Death related to advanced chronic liver disease (ACLD) is often heralded by a prolonged decline. Clinical encounters therefore represent key opportunities for advanced care planning (ACP) and optimised EOLC in this cohort, supported by specialist palliative care services (SPCS). However, the limitations of current provision are increasingly recognised. We reviewed practice across South West England to identify patient and service factors associated with ACP and referral to SPCS. Methods: We conducted a retrospective observational study of patients who died of ACLD between 1st February 2019 and 31st January 2020. Patients required at least one non-terminal ACLD-related admission in their last year of life. Patient and service variables were recorded from interrogation of electronic records. The primary outcome was of documented discussions regarding ACLD and ACP. The secondary outcome was referral to SPCS. Statistical analysis, including multivariate regression, was performed using Stata V16 (StataCorp2019). Results: Ten sites contributed data with 204 patients included for analysis. ACLD and ACP were discussed with 39.7% and 27.9% of patients respectively, mostly within the last three months of life. ACP discussion was significantly more likely in those with drain-dependent ascites (OR 2.57[p=0.007]), more than three outpatient clinics within the last year of life (OR 2.51[p=0.046]) and in non-alcoholic fatty liver disease (NAFLD) compared to alcohol-related liver disease (ArLD) (OR 4.06 [p=0.002]). Documentation of MELD/Child-Pugh was also associated with earlier discussion, but such documentation occurred in only 17.2% of patients. 32.8% of patients received inpatient specialist palliative care, though 75% of these referrals only occurred during a terminal admission. Provision of a dedicated inpatient hepatology service was associated with increased inpatient SPCS involvement (OR 3.40 [p=0.001]). Only 26% of patients were referred to outpatient SPCS. Discussion: Despite the availability of prognostic tools, most patients were not offered ACP planning and specialist palliative care input was largely limited to a late stage in the patient journey. Differences in provision between NAFLD and ArLD might reflect predictability of disease trajectory, level of service engagement or potentially negative discrimination. We have demonstrated patient and service factors associated with improved EOLC, yet critical areas of need have been highlighted. Moving forwards our goal is to promote a parallel care model across South West England, with earlier palliative care offered alongside ongoing active management.